Ginsenoside Rg3 exhibits anti-catabolic and anti-apoptotic effects in IL-1β treated human disc nucleus pulposus cells and in a rat model of disc degeneration by inactivating the MAPK pathway: Ginsenoside Rg3 regulates IDD by MAPK - Chen, Jie; Zhang, Bin; Wu, Liwei; Xu, Jiabin (Cellular and Molecular Biology, 2024)
Intervertebral disc degeneration (IDD) is the major cause of degeneration of joint diseases. IDD is characterized by a large number of apoptosis of nucleus pulposus cells (NPCs) and extracellular matrix (ECM) degradation. Ginsenoside Rg3 is the active component extracted from ginseng and has a vital function in modulating diseases. This study aimed to investigate the regulatory functions of ginsenoside Rg3 in IDD. We established the IDD cell model via inducing NPCs with IL-1β. The rat model of IDD was established by fibrous ring puncture method. Cell apoptotic capability was assessed through TUNEL assay. The levels of catabolic proteases MMPs and ADAMTSs were tested by western blot and RT-qPCR. IL-1β induction notably promoted the apoptosis of NPCs, while ginsenoside Rg3 treatment reversed the promoting function of IL-1β. Furthermore, we found that MMP2, MMP3, Adamts4, and Adamts5 levels were increased in IL-1β-induced NPCs, while ginsenoside Rg3 treatment markedly reduced their levels. Additionally, ginsenoside Rg3 was found to suppress the IL-1β-stimulated p38 MAPK pathway in NPCs. In the IDD rat model, we found that ginsenoside Rg3 treatment can alleviate NPC degeneration, recover the arrangement of annulus fibrous, and preserve more proteoglycan matrix. Moreover, ginsenoside Rg3 reduced apoptosis and catabolism and inactivated the p38 MAPK pathway in IDD rats. Ginsenoside Rg3 exhibits anti-catabolic and anti-apoptotic effects in IL-1β-stimulated NPCs and IDD rats by inactivating MAPK pathway.